Beta-thromboglobulin in cerebral infarction. Issue 4 (April 1988) - Woo, E; Huang, C Y; Chan, V; Chan, Y W; Yu, Y L; Chan, T K
Abstract : Plasma beta-thromboglobulin (BTG) was significantly elevated in the acute phase of 116 atherosclerotic thrombotic (p less than 0.0001) and 36 cardioembolic (p less than 0.005) infarcts but normal for 96 lacunes compared with controls. This elevation persisted into the 6th week after the acute event. Among atherosclerotic thrombotic infarcts, the acute beta-thromboglobulin level showed a tendency to correlate with infarct size on CT and predicted mortality at 6 weeks. These results suggest that platelet aggregation plays a primary role in the pathogenesis of atherothrombosis.